INVESTIGATION OF DECODING FILLERS USED IN AN ENGLISH LEARNING TALK SHOW “ENGLISH WITH ALICE” - Ridwin Purba; Herman Herman; Veronika R. M Manullang; Magdalena Ngongo (University of Kuningan, 2021)
This research was conducted to analyze decoding fillers in English learning talk show. The researchers made two groups of non-native English speakers to investigate fillers, Group one with little or no abroad experienced speakers and Group two with long term abroad experienced speakers. The researchers used descriptive qualitative as a method that describes an objective situation or certain event based on facts that appear or should be followed by an attempt to draw general conclusion. The procedure is ethnographic research which is ethnographic by qualitative enable researchers to understand the data by the functions of language (words, phrase and sentence) by grouping words that have same functions into categories. The researchers would analyze and conclude the data to be studied. In this research the data to be reviewed is English with Alice which contain fillers. The researchers found one hundred sixty-eight fillers with the exclusion of filler used by the host and both of speakers. After analyzing the data, the researchers found that 2 groups (14 guests) in the talk show English with Alice used different functions of decoding fillers. The functions in Group one are mostly (a) to begin and close a discourse and (c) to hold the floor. Moreover, the functions in Group two are mostly (c) to hold the floor and (g) to express the response.